Assessing Economic Value of a Cultural Heritage Site Using Travel Cost Method - Annisa Zahrah Pramono; Endah Saptutyningsih (Journal of Economics Research and Social Sciences, 2023)
This study aims to calculate the economic value and analyze the effect of independent variables (travel costs, age, education, income, satisfaction, residence, time spent, and facility) on the number of tourists visits to Sonobudoyo Museum of Yogyakarta, Indonesia. This study uses primary data with a total of 257 tourist. The calculation of economic value is carried out using the Travel Cost Method approach to to Sonobudoyo Museum tourist objects in Yogyakarta. Analyzer in this research is multiple linear regression. The results of this study indicate that variable travel cost, income, satisfaction, and time spent has a significant effect while the other variable such as age, education, residence, and facility have no effect on the number of tourists visit to Sonobudoyo Museum. It is also known that the economic value of Sonobudoyo Museum is IDR 5,461,932,433 per year.